PENENTUAN ZONA MINERALISASI LOGAM MENGGUNAKAN INTEGRASI METODE MAGNETIK DAN POLARISASI INDUKSI DENGAN GEOLOGI DI KECAMATAN PRONOJIWO, KABUPATEN LUMAJANG, PROVINSI JAWA TIMUR: METAL MINERALIZATION ZONES DETERMINATION USING INTEGRATION OF MAGNETIC AND INDUCTION POLARIZATION METHODS WITH GEOLOGY IN PRONOJIWO DISTRICT, LUMAJANG REGENCY, EAST JAVA PROVINCE - Mambai, Hillary Inri; Dzil Mulki Heditama; Edya Putra (Buletin Sumber Daya Geologi, 2026)
Research area is located in Pronojiwo District, Lumajang Regency, which is physiographically located in the Sunda-Banda Magmatic Arc, an area with high metal mineralization potential. This study aims to identify and characterize prospective zones of gold (Au) and copper (Cu) mineralization through the integration of magnetic and Induced Polarization (IP) data. Primary data in the form of 410 magnetic measurement points and secondary data in the form of four IP lines (resistivity and chargeability) as well as regional geological data are used for validation and interpretation of mineralization zones through 2D inversion modeling. The processing results show a distribution of magnetic anomalies with values ​​ranging from 0.4 to 8.1 nT/m on the analytic signal map and -325.5 to 577.3 nT on the residual magnetic anomaly map. The integration of magnetic and IP data successfully identified two main prospect zones: Zone A as a potassic alteration zone with high chargeability, intermediate resistivity, and high magnetic susceptibility, indicating the core zone of a porphyry deposit system with potential Cu-Au accumulation and Zone B as a phyllic alteration zone with high chargeability, high resistivity, and low magnetic susceptibility, representing an intermediate alteration zone with disseminated sulfide mineralization. Zone A is the main exploration target because it is located in the center of the porphyry system, while Zone B is not a main target, but helps describe the distribution of alteration and shows how the hydrothermal system develops around the core zone. The integration of magnetic and IP methods is effective in delineating alteration zones and supporting further exploration.